Congress after Indira policy, power, political change (1984-2009) - Hasan, Zoya. (New Delhi : Oxford University Press, 2013)
This text provides a thematic account of political processes and discursive policy practices and shifts which shaped the thinking and approach of the Indian National Congress. It assesses the impact of transformation in economy, society, and polity on the Congress. The volume interprets the politics of change in India and how this developed Congress policies, especially under the United Progressive Alliance.
Description based on online resource; title from home page (viewed on Dec. 20, 2012).
Includes bibliographical references and index.
Keywords: Indian National Congress; India -- Politics and government -- 1977-